1962
DOI: 10.1073/pnas.48.3.379
|View full text |Cite
|
Sign up to set email alerts
|

EXTINCTION OF EXPERIMENTAL MAMMARY CANCER, I. ESTRADIOL-17β AND PROGESTERONE

Abstract: PATHOLOGY: HUGGINS, MOON, AND MORIH 379 days, the culture was green and thriving. This strain has been isolated and designated Chlorella pyrenoidosa C-37-2-G4. The modified strain grows well in the presence of progesterone. Cultures of the modified strain to which progesterone has been added deteriorate at a much slower rate than those cultures of the original strain to which androstenedione or dehydroisoandrosterone had been added. Furthermore, thin-layer silica-gel chromatography indicates that metabolic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
66
0

Year Published

1962
1962
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(70 citation statements)
references
References 5 publications
4
66
0
Order By: Relevance
“…The data reported in this study show that the natural hormone progesterone accelerates the development of DMBAinduced mammary tumors, confirming earlier reports in the literature (28,29,38). In this study, progesterone was found to increase the incidence and size of tumors when compared with the placebo control group; however, like the low-dose MPA results, it did not change the latency period compared with controls.…”
Section: Discussionsupporting
confidence: 91%
“…The data reported in this study show that the natural hormone progesterone accelerates the development of DMBAinduced mammary tumors, confirming earlier reports in the literature (28,29,38). In this study, progesterone was found to increase the incidence and size of tumors when compared with the placebo control group; however, like the low-dose MPA results, it did not change the latency period compared with controls.…”
Section: Discussionsupporting
confidence: 91%
“…The use of hormones for inhibiting mammary carcinogenesis has been explored by several authors (Dao et al, 1960;Dao & Sutherland, 1959;Grubbs et al, 1983aGrubbs et al, ,b, 1986Huggins et al, 1961Huggins et al, , 1962McCormick & Moon, 1965Welsch, 1985). Among the hormones tested for this purpose have been treatment with oestrogen and progesterone at different doses (Grubbs et al, 1983b;McCormick et al, 1965), although hormone deprivation through ovariectomy or administration of the anti-oestrogen tamoxifen also inhibits mammary carcinogenesis (Welsch, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Progesterone and breast cancer have been linked since the concept of hormone-dependent cancers was first elaborated (1)(2)(3). The steroid hormone has been implicated in both the genesis and the extinction of experimentally induced mammary tumors (2)(3)(4)(5).…”
mentioning
confidence: 99%